Investor Attention and Cryptocurrency Returns: Evidence from Quantile Causality Approach. Issue 1 (2nd January 2020) - Subramaniam, Sowmya; Chakraborty, Madhumita
Abstract: The erratic price behavior and inefficiency in the crypto markets offer possibility to examine the behavioral aspects in cryptocurrency prices. Further, the cryptocurrency market is dominated by the retail investor providing an interesting platform to examine the impact of attention-driven trading in this particular asset class. Thus, the authors investigate the influence of investor attention in the cryptocurrency prices using the quantile causality approach. The results indicate that investors pay attention to the frequent news-making and ranked cryptos (Bitcoin and Ethereum). For newer cryptocurrencies like Ripple, investor attention influences their prices only during superior performance. The study provides evidence of attention-induced price pressure hypothesis in the prices of cryptocurrencies during expansionary phases and fear selling during poor market performance.